Culture and Nationalism in Devkota’s Shakuntala - Sharma, Bal Krishna (Bodhi: An Interdisciplinary Journal, 2010)
Laxmi Prasad Devkota's reputation as one of the most accomplished literary figures in Nepal needs any elaborate explication. A cursory glance at his English writings reveals that he was as good in English language as in Nepali. His English renderings include essays, poems and translations. Kafle (2007) puts Devkota's English writings in three categories: first, those originally written in English; second, the translations of his own works; and third, the translations of other contemporary writers (p. 19). The famous epic Shakuntala is considered greatest among his works written both in English and Nepali. DOI: 10.3126/bodhi.v2i1.2872 Bodhi Vol.2(1) 2008 p.205-210